Dynamic reserve calculation method for gas-condensate reservoirs based on flowing material balance theory - ZHAO Lingbo, DUAN Yonggang, LUO Le, ZHOU Jinxin (Youqicang pingjia yu kaifa)
The depletion process of a gas-condensate reservoir is characterized by significant condensation phenomenon. Existing material balance methods often fail to establish a linear relationship between pressure drop and cumulative production, resulting in considerable errors in dynamic reserve evaluations. Therefore, it is crucial to study material balance methods tailored for complex multiphase flow gas reservoirs. Based on the fluid flow poromechanics of gas-condensate reservoirs, a new method for calculating dynamic reserves in gas-condensate reservoirs was established by introducing two-phase pseudo-pressure parameter and applying flowing material balance theory. In the multiphase flowing material balance method, a clear linear relationship was observed between the normalized production rate and normalized cumulative production. The analysis results showed that when the production did not reach the pseudo-steady state, the calculated dynamic reserve results would be biased. By analyzing the differences in saturation behavior across various flow regimes, a calculation method for the two-phase pseudo-pressure parameter was developed. The modified production indication curve could improve the accuracy of dynamic reserve calculations for condensate gas reservoirs. The method was applied to wells in a gas-condensate reservoir. Compared with conventional methods and the Blasingame chart fitting method, the proposed approach yielded more accurate dynamic reserve evaluations. The results demonstrate that the proposed calculation method enhances the accuracy of dynamic reserve evaluations for gas-condensate reservoirs and supports timely adjustments to development plans in the field.